Profitability determinants of Islamic and conventional banks in Malaysia: a panel regression approach - Abduh, Muhamad; Omar, Mohd. Azmi; Mesic, Edina (Universiti Teknologi MARA Terengganu, 2013)
This paper examines the impact of bank-specific and macroeconomic factors upon the profitability performance of Islamic and conventional banks in Malaysia using panel data regression analysis. The sample comprises of seventeen conventional banks and thirteen Islamic banks covering the period of 2005-2009. The results show that liquidity ratios and macroeconomic condition are the profitability determinant under pooled OLS framework, while only liquidity ratio is significantly affecting profitability under random effects model. However, final result under fixed effects model shows that types of bank and macroeconomic condition are the significant determinants of bank profitability. This study also evidences that Islamic banks are more profitable than conventional banks during the period analyzed.